Knife‐assisted snare resection (KAR) of large and refractory colonic polyps at a Western centre: Feasibility, safety and efficacy study to guide future practice. Issue 3 (1st June 2016) - Bhattacharyya, Rupam; Chedgy, Fergus JQ; Kandiah, Kesavan; Longcroft‐Wheaton, Gaius; Bhandari, Pradeep
Abstract : Objective: Endoscopic mucosal resection (EMR) is widely practiced in western countries. Endoscopic submucosal dissection (ESD) is very effective for treating complex polyps but colonic ESD in the western setting remains challenging. We have developed a novel technique of knife‐assisted snare resection (KAR) for the resection of these complex lesions. Here we aim to describe the technique, evaluate its outcomes, identify outcome predictors and define its learning curve. Methods: We conducted a prospective cohort study of patients who had large and refractory polyps resected by KAR at our institution from 2007 to 2013. Polyp characteristics and procedure details were recorded. Endoscopic follow‐up was performed to identify recurrence. Results: A total of 170 patients with polyps 20–170 mm in size were treated by KAR and followed up for a mean of 31.5 months (range 12–84 months). 29% of the polyps were >50 mm, 22% had fibrosis from previous unsuccessful interventions and 25% were in the right colon. The perforation rate (1.2%) and bleeding rate (4.7%) were acceptable and managed conservatively in most patients. Recurrence rate after the first attempt was 13.1%. Recurrence was significantly increased by polyp size >50 mm ( p = 0.008; OR 5.03, 95% CI 1.54–16.48), presence of fibrosis ( p = 0.002; OR 6.59, 95% CI 1.97–22.07) and piecemeal resection ( p < 0.001; OR 0.31, CI 0.078–1.12). Cure rates were 87% after the first attempt, improving to 95.6% with further attempts. En bloc resection rate showed a linear increase and reached almost 80% as the endoscopist's cumulative experience approached 100 cases. Conclusion: This is the largest reported Western series on KAR in the colon. We have demonstrated the feasibility, efficacy and safety of this technique in the treatment of complex polyps, with or without fibrosis and at all sites. KAR has shown better outcomes than either EMR or ESD. We have also managed to identify significant outcome predictors and define the learning curve.